This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
S = sin 6 1 + sin 6 2 + . . . + sin 6 8 8 + sin 6 8 9
Keeping in mind that s i n X = c o s ( 9 0 − X ) , this means s i n 6 X = c o s 6 ( 9 0 − X )
Therefore we have our sum:
S = sin 6 1 + sin 6 2 + . . . + sin 6 4 4 + sin 6 4 5 + cos 6 ( 9 0 − 4 6 ) + . . . + cos 6 ( 9 0 − 8 8 ) + cos 6 ( 9 0 − 8 9 )
Which simplifies to:
S = sin 6 1 + sin 6 2 + . . . + sin 6 4 4 + sin 6 4 5 + cos 6 4 4 + . . . + cos 6 2 + cos 6 1
Since,
sin 4 5 = 2 2 then, sin 6 4 5 = 8 1 and also,
sin 6 X + cos 6 X = ( 1 − 3 s i n 2 X c o s 2 X )
So going back to our sum:
S = sin 6 1 + sin 6 2 + . . . + sin 6 8 8 + sin 6 8 9
S = ( 1 − 3 s i n 2 1 c o s 2 1 ) + ( 1 − 3 s i n 2 2 c o s 2 2 ) + . . . + ( 1 − 3 s i n 2 4 4 c o s 2 4 4 ) + sin 6 4 5
Adding all the ones and factoring out a -3: S = 4 4 + 8 1 − 3 ( s i n 2 1 c o s 2 1 + s i n 2 2 c o s 2 2 + . . . + s i n 2 4 4 c o s 2 4 4 )
Since s i n 2 X = 2 s i n X c o s X , lets write the above equation as:
S = 4 4 + 8 1 − 4 3 ( 4 s i n 2 1 c o s 2 1 + 4 s i n 2 2 c o s 2 2 + . . . + 4 s i n 2 4 4 c o s 2 4 4 )
We did this because 4 s i n 2 X c o s 2 X = 2 s i n 2 2 X
Therefore our sum can be written, and simplified as:
S = 8 3 5 3 − 4 3 ( s i n 2 2 + s i n 2 4 + . . . + s i n 2 4 4 + s i n 2 4 6 + . . . + s i n 2 8 8 )
S = 8 3 5 3 − 4 3 ( s i n 2 2 + s i n 2 4 + . . . + s i n 2 4 4 + c o s 2 ( 9 0 − 4 6 ) + . . . + c o s 2 ( 9 0 − 8 6 ) + c o s 2 ( 9 0 − 8 8 ) )
S = 8 3 5 3 − 4 3 ( s i n 2 2 + s i n 2 4 + . . . + s i n 2 4 4 + c o s 2 4 4 + . . . + c o s 2 4 + c o s 2 2 )
S = 8 3 5 3 − 4 3 ( s i n 2 2 + c o s 2 2 + s i n 2 4 + c o s 2 4 + . . . + s i n 2 4 4 + c o s 2 4 4 )
And s i n 2 X + c o s 2 X = 1 , therefore
S = 8 3 5 3 − 4 3 ( 2 2 )
S = 8 3 5 3 − 8 1 3 2
S = 8 2 2 1
S = 2 7 . 6 2 5